A CD2 high‐expressing stress‐resistant human plasmacytoid dendritic‐cell subset. Issue 5 (16th February 2016) - Bryant, Christian; Fromm, Phillip D; Kupresanin, Fiona; Clark, Georgina; Lee, Kenneth; Clarke, Candice; Silveira, Pablo A; Suen, Hayley; Brown, Ross; Newman, Elizabeth; Cunningham, Ilona; Ho, P Joy; et al.
Abstract : Human plasmacytoid dendritic cells (pDCs) were considered to be a phenotypically and functionally homogeneous cell population; however, recent analyses indicate potential heterogeneity. This is of major interest, given their importance in the induction of anti‐viral responses and their role in creating immunologically permissive environments for human malignancies. For this reason, we investigated the possible presence of human pDC subsets in blood and bone marrow, using unbiased cell phenotype clustering and functional studies. This defined two major functionally distinct human pDC subsets, distinguished by differential expression of CD2. The CD2 hi and CD2 lo pDCs represent discontinuous subsets, each with hallmark pDC functionality, including interferon‐alpha production. The rarer CD2 hi pDC subset demonstrated a significant survival advantage over CD2 lo pDC during stress and upon exposure to glucocorticoids (GCs), which was associated with higher expression of the anti‐apoptotic molecule BCL2. The differential sensitivity of these two human pDC subsets to GCs is demonstrated in vivo by a relative increase in CD2 hi pDC in multiple myeloma patients treated with GCs. Hence, the selective apoptosis of CD2 lo pDC during stress represents a novel mechanism for the control of innate responses.